PLASTIC CHAIR VERSATILITY AS AN APPROACH TO CONSTRUCT PASAR 1 BARU INFORMAL SPACE - Roland Tejo Prayitno; Yandi Andri Yatmo; Paramita Atmodiwirjo (Dimensi: Journal of Architecture and Built Environment, 2019)
This paper investigates materiality as architecture manifestation in commercial informal space. The materialityapproach in this paper revolves around the Manuel De Landa idea of material’s properties and capacity, whichinteract to each other to create unlimited possibilities. This cycle of interaction is what Manuel DeLanda called as morphogenic power of its own. Understanding material system and existing context are two essential processin order to produce a responsive design in this random, unpredictable pattern of informal space, which in this paper, the context that will be specifically studied is Pasar Baru. In the further study, the material which will bestudied along with Pasar Baru context is the versatile usage of plastic chair. This paper will investigate materiality approach as a relevant method to create a contextual design, as this approach will be highly based oninteraction system between the physical material and the context.